Environmental enrichment reduces brain excitability in adult rats overnourished during lactation - Danielle Viana de Souza Alves; Mariana Séfora Bezerra Sousa; Maryane Gabriela Tavares; Luis Gustavo Carvalho dos Santos; Manuella Batista-de-Oliveira-Hornsby; Angela Amancio-dos-Santos (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: This study aimed to analyze whether exposure to environmental enrichment (EE) during the juvenile phase of life interferes with the electrical activity of the adult rat brain. In addition, the present research also investigated whether this putative effect on brain electrical activity could be affected by prior overnutrition during lactation. Electrophysiology was measured through cortical spreading depression (CSD), a phenomenon related to brain excitability. Methods: Wistar rats were suckled in litters of either nine or three pups, forming the nourished (N) or overnourished (ON) groups, respectively. At 36 days old, half of the animals from each nutritional condition were exposed to EE. The other half was kept in the standard environment (SE). At 90-120 days of life, each animal was anesthetized for CSD recordings. Results: Overnutrition during lactation caused increases (p < 0.05) in body and brain weights. The EE decelerated CSD propagation velocity regardless of nutritional state during lactation (p < 0.001). The CSD deceleration in the N-EE group was 23.8% and in the ON-EE group was 15% in comparison with the N-SE and ON-SE groups, respectively. Conclusion: Our data demonstrated that EE exposure in the juvenile phase of the rat's life reduced brain excitability, and this effect was observed even if animals were overnourished during lactation. An EE could be considered an adjuvant therapeutic resource to modulate brain excitability.